A Regime View of the North Atlantic Oscillation and Its Response to Anthropogenic Forcing - Woollings, T; Hannachi, A; Hoskins, B; Turner, A (2010)
The distribution of the daily wintertime North Atlantic Oscillation (NAO) index in the 40-yr ECMWF Re-Analysis (ERA-40) is significantly negatively skewed. Dynamical and statistical analyses both suggest that this skewness reects the presence of two distinct regimes-referred to as "Greenland blocking" and "sub-polar jet." Changes in both the relative occurrence and in the structure of the regimes are shown to contribute to the long-term NAO trend over the ERA-40 period. This is contrasted with the simulation of the NAO in 100-yr control and doubled CO2 integrations of the third climate configuration of the Met Office Unied Model (HadCM3). The model has clear deficiencies in its simulation of the NAO in the control run, so its predictions of future behavior must be treated with caution. However, the subpolar jet regime does become more dominant under anthropogenic forcing and, while this change is small it is clearly statistically signicant and does represent a real change in the nature of NAO variability in the model. © 2010 American Meteorological Society.